Augmented Reality and Mobile Augmented Reality in Education: A Thematic Analysis of Studies in Turkey - Yildirim, Pelin; Kececi, Gonca (Springer, 2026)
This research aims to evaluate a total of 122 master’s and doctoral theses focusing on Augmented Reality (AR) and Mobile Augmented Reality (MAR) applications in the field of education between 2020 and May 2024. The data source used was the National Thesis Center database, which centrally collects postgraduate theses in Turkey. However, full-text access to all theses was not possible during the research period, and some theses were examined only through their abstracts. Additionally, some theses are accessible only as printed copies via the Turkish Document Supply and Loan System due to confidentiality (embargo), personal preferences, or institutional policies. This situation limited the sample size and the scope of the analysis. The thesis contents were analyzed using a matrix. The results showed that master’s theses were more common than doctoral theses. While a general increase in AR and MAR-related theses was observed, a decline was recorded due to incomplete data for 2024. Studies in fields such as Computer and Instructional Technologies Education were prominent. Furthermore, various thematic focuses such as academic achievement, opinions, attitudes, and motivation in education were examined. Researchers frequently preferred quasi-experimental and mixed methods; sample sizes generally ranged from 30 to 100, and SPSS software was commonly used. To increase the number of doctoral theses in AR and MAR fields, research scholarships and support programs for doctoral students should be organized, and graduate programs and research funds should be supported. © The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2025.
Keywords: Augmented reality; Education; Mobile augmented reality; Thematic content analysis